MR guided thermal therapy of pancreatic tumors with endoluminal, intraluminal and interstitial catheter-based ultrasound devices: Preliminary theoretical and experimental investigations - Prakash, Punit (2013)
Image-guided thermal interventions have been proposed for potential palliative and curative treatments of pancreatic tumors. Catheter-based ultrasound devices offer the potential for temporal and 3D spatial control of the energy deposition profile. The objective of this study was to apply theoretical and experimental techniques to investigate the feasibility of endogastric, intraluminal and transgastric catheter-based ultrasound for MR guided thermal therapy of pancreatic tumors. The transgastric approach involves insertion of a catheter-based ultrasound applicator (array of 1.5 mm OD x 10 mm transducers, 360° or sectored 180°, ~7 MHz frequency, 13–14G cooling catheter) directly into the pancreas, either endoscopically or via image-guided percutaneous placement. An intraluminal applicator, of a more flexible but similar construct, was considered for endoscopic insertion directly into the pancreatic or biliary duct. An endoluminal approach was devised based on an ultrasound transducer assembly (tubular, planar, curvilinear) enclosed in a cooling balloon which is endoscopically positioned within the stomach or duodenum, adjacent to pancreatic targets from within the GI tract. A 3D acoustic bio-thermal model was implemented to calculate acoustic energy distributions and used a FEM solver to determine the transient temperature and thermal dose profiles in tissue during heating. These models were used to determine transducer parameters and delivery strategies and to study the feasibility of ablating 1–3 cm diameter tumors located 2–10 mm deep in the pancreas, while thermally sparing the stomach wall. Heterogeneous acoustic and thermal properties were incorporated, including approximations for tumor desmoplasia and dynamic changes during heating. A series of anatomic models based on imaging scans of representative patients were used to investigate the three approaches. Proof of concept (POC) endogastric and transgastric applicators were fabricated and experimentally evaluated in tissue mimicking phantoms, ex vivo tissue and in vivo canine model under multi-slice MR thermometry. RF micro-coils were evaluated to enable active catheter-tracking and prescription of thermometry slice positions. Interstitial and intraluminal ultrasound applicators could be used to ablate (t(43)>240 min) tumors measuring 2.3–3.4 cm in diameter when powered with 20–30 W/cm(2) at 7 MHz for 5–10 min. Endoluminal applicators with planar and curvilinear transducers operating at 3–4 MHz could be used to treat tumors up to 20–25 mm deep from the stomach wall within 5 min. POC devices were fabricated and successfully integrated into the MRI environment with catheter tracking, real-time thermometry and closed-loop feedback control.